Valor prognóstico da imunoexpressão de p53 em neoplasias mamárias de cadelas - Moreira, Thaís de Almeida (2018)
Breast cancer is the most important neoplasm in intact bitches. Mutations in p53 tumor suppressor gene lead to overexpression of p53 protein in mammary neoplasms and have been associated a worse prognosis in women, but its prognostic value in canine mammary tumors (CMT) is controversial. The aim of this study was evaluate the p53 expression in CMT and verify its correlation with clinical, pathological, tumor features and overall survival (OS), also evaluating the disease free interval (DFI) and tumor development interval in the breast remnant (TDIBR) of bitches submitted to partial mastectomy. One hundred bitches were followed up for a minimum of two years. Determination of p53 expression was performed by immunohistochemistry using the streptavidin-biotin-peroxidase technique. Samples with more than 10% of labeled neoplastic cells were considered positive, which were also evaluated for percentage and marking intensity. P53 overexpression was found in 65% (65/100) of the tumors. There was a correlation between p53 overexpression and histological subtype, which was higher in tubular and complex carcinomas (p = 0.017), and a higher marker score and higher labeling intensity was observed in high histological grade neoplasms (p = 0.023 and p = 0.030, respectively). However, there was no correlation between p53 expression and DFI (p = 0.441) and TDIBR (p = 0.240). The age of the dog at diagnosis was a factor that also influenced OS, being worse in bitches with more than eight years (p = 0.023). This study demonstrated that the p53 overexpression in CMT should be considered as an important prognostic factor, related to a worse survival.